Structural Characteristics and Diffusion Coefficient of Alginate Hydrogels Used for Cell Based Drug Delivery. (22nd May 2018) - Najdahmadi, Avid; Lakey, Jonathan RT; Botvinick, Elliot
ABSTRACT: Alginate is a hydrogel polymer commonly used in multiple drug delivery and cellular tissue transplantation applications. Tunability, gel formation, and stabilization properties of this biopolymer contributes to a better controlled and prolonged release of encapsulated drugs as well as the ability to provide immunoisolation to transplanted cells. One commonly used application of this biopolymer is pancreatic islet transplantation, as a promising approach of providing insulin to type 1 diabetics. The encapsulant alginate provides passage to nutrients, glucose and oxygen and allows the insulin to diffuse while blocking immunoglobulins. In this study, a hydrogel encapsulator is designed and used to fabricate spherical alginate microcapsules. These capsules are then incubated in either a calcium chloride solution typical used to polymerize alginate or a physiological media formulated to mimic in vivo conditions. The diffusion of different molecular weight particles tagged with spectrally distinct fluorescent molecules into the microspheres is observed using confocal laser microscopy. We characterize changes in diffusional characteristics of these molecules within alginate spheres as a function of incubation duration. We estimate diffusion coefficients (D) from fluorescence image series and observe a notable increase in capsule permeability once incubated in physiological media. Our strategy can serve as quantitative method to analyze structural changes in hydrogels.